Research on Formation Mechanism and Evolution Pattern of Bed Separation Zone during Repeated Mining in Multiple Coal Seams - Jianshuai Ji; Zhihua Li; Ke Yang; Guanghua Zhou; Guojun Ma; Cheng Liu; Peng Zhou (Geofluids, 2022)
Mastering the formation mechanism and dynamic evolution pattern of bed separation zone during repeated mining is the key to the success or failure of separation grouting injection technology. Taking a mine in Ningdong as the engineering background, using the research methods of theoretical analysis, numerical simulated, and field measurement, four overburden structure models of single or multiple key strata with repeated mining and single or multiple key strata without repeated mining were constructed. The evolution pattern of bed separation zone was studied from four aspects: bed separation zone development mechanism, formation position, development form, and change of clearance. The results showed that when a single key stratum of repeated mining exists between coal seams, it is difficult to form a large separation area because there is no key stratum during the upper coal mining, and a separation area will be formed below the key stratum when mining the lower coal. When the key stratum exists above all coal seams, a large separation zone will be formed under the key stratum when the upper coal is mined. When mining the lower coal, when the coal seam spacing is less than 4 times of the mining height of the lower coal, the crack will penetrate the upper coal floor. If the key stratum is not completely broken, secondary separation may occur. When multiple key strata are all located above all coal seams, there will be bed separation zone under the high-level key stratum. When multiple key strata and coal seams are distributed at intervals, the separation below the high-level key stratum during upper coal mining and the separation below the low-level key stratum during lower coal mining are formed. Because the high-level key stratum bends and sinks after being affected by the mining of coal 1, the clearance of bed separation during mining coal 2 is slightly less than that during mining coal 1, which is contrary to the pattern that the greater the bed separation clearance increases with the increase of mining height.